"Managerial economics; theory, applications and cases 4th ed" - "Mansfield,Edwin" (New York, 1999)
This book presents the economics underlying a wide range of managerial decisions and corporate strategies. Among its definitive strengths are Professor Edwin Mansfield's prowess in linking economic theory to real applications in the business world, the unmatched clarity and care of his exposition, and his outstanding credentials as both an economic researcher and a consultant to numerous businesses and organizations. This new edition features expanded coverage of the important fields of game theory and strategic behavior, and a wide range of new cases and applications.
Keywords: Managerial economics